Knitty gritty murder - Ehrhart, Peggy (Ehrhart, Peggy. Knit & Nibble mystery., 2021)
"Most times of the year, the tight-knit community gardens in quaint Arborville, New Jersey, overflow with seasonal vegetables and herbs. But who planted the dead body? Farm-to-table enthusiast Jenny Miller had a cookbook in the works when she was suddenly found strangled by a circular knitting needle in her own plot. Now, the pressure is on Pamela and her neighbor Bettina as they weave together clues in search of the person who kept Jenny's renowned heirloom plants--and budding career--from growing"--